1D Bi2S3 nanorods modified 2D BiOI nanoplates for highly efficient photocatalytic activity: Pivotal roles of oxygen vacancies and Z-scheme heterojunction. (10th April 2023) - Ju, Peng; Zhang, Yu; Hao, Lei; Cao, Jiazhen; Zhai, Xiaofan; Dou, Kunpeng; Jiang, Fenghua; Sun, Chengjun
Highlights: Novel hierarchical network-like Bi2 S3 /Bi5 O7 I Z-scheme heterojunctions were prepared by an in-situ ion exchange method. BSBI NHs were consisted of internal BiOI nanoplates and outside networks orderly interwoven by Bi2 S3 nanorods. BSBI NHs displayed a significantly improved visible-light photocatalytic ability. Z-scheme heterojunction and massive OVs resulted in the efficient separation of photogenerated charge carriers. ∙OH, ⋅O2 − and h + played primary roles during the photocatalytic process. Abstract: In this study, a novel Bi2 S3 /BiOI Z-scheme photocatalyst with 3D porous hierarchical network-like heterostructure (BSBI NHs) and rich oxygen vacancies (OVs) was fabricated by a facile ion exchange method followed by the in-situ growth process. A possible formation mechanism of BSBI NHs was studied, showing the self-assembled process of in-situ interwoven growth of 1D Bi2 S3 nanorods (NRs) on the surface of 2D BiOI disk-like nanoplates (NPs), which followed the Ostwald ripening and epitaxial growth. The modification of BiOI NPs by Bi2 S3 NRs brought about the formation of Z-scheme heterojunction and massive OVs, which improved the visible-light response property and promoted the separation of photoexcited charge carriers of BSBI NHs. BSBI NHs exhibited a significantly enhanced photocatalytic activity compared with Bi2 S3 and BiOI, and BSBI-1 can remove almost all bacteria and Rhodamine B (RhB) after 60 min visible light illumination. In addition, the photocatalytic mechanism was studied and speculated based on the tests of active species capture, electron spin resonance (ESR), and density functional theory (DFT) simulation calculation, proving the primary roles of ·OH, ·O2 – and h + during the photocatalytic reaction. This work provides new insights into the design and exploitation of novel heterojunctions with highly efficient photocatalytic performances for environmental remediation applications.